2007
DOI: 10.14411/eje.2007.022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of poor host-parasitoid synchronisation on the parasitism of Cameraria ohridella (Lepidoptera: Gracillariidae)

Abstract: Abstract. Poor synchronisation is considered to be one important reason for the ineffective control of the invasive horse chestnut leafminer by native parasitic Hymenoptera. Parasitoids hibernating in dry horse chestnut leaves break diapause early in spring and presumably leave the vicinity, since no hosts are available when they emerge. As a consequence, the percentage parasitism of the first generation of the leafminer in early summer is low. The experiments presented below were designed to test this hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
(18 reference statements)
2
13
0
Order By: Relevance
“…There was a two-week delay in peak moth emergence in 2014 compared to 2013, which was most likely due to differences in temperature during winter and early spring. The results also revealed that parasitoids started to emerge from fallen leaves earlier than horse chestnut leaf-miner, which is well documented by many authors (Hellrigl, 2003;Grabenweger, 2004;Grabenweger et al, 2007). Poor synchronization between parasitoid emergence and C. ohridella development is believed to be the reason for the lack of control of this species in the fi rst generation (Grabenweger, 2004), but does not signifi cantly affect the abundance of the most important parasitoid in the complex, Minotetrastichus frontalis, and consequently has no effect on the parasitism of C. ohridella (Grabenweger et al, 2007).…”
Section: Emergence Of C Ohridella and Its Parasitoids From Leaf Littsupporting
confidence: 81%
See 2 more Smart Citations
“…There was a two-week delay in peak moth emergence in 2014 compared to 2013, which was most likely due to differences in temperature during winter and early spring. The results also revealed that parasitoids started to emerge from fallen leaves earlier than horse chestnut leaf-miner, which is well documented by many authors (Hellrigl, 2003;Grabenweger, 2004;Grabenweger et al, 2007). Poor synchronization between parasitoid emergence and C. ohridella development is believed to be the reason for the lack of control of this species in the fi rst generation (Grabenweger, 2004), but does not signifi cantly affect the abundance of the most important parasitoid in the complex, Minotetrastichus frontalis, and consequently has no effect on the parasitism of C. ohridella (Grabenweger et al, 2007).…”
Section: Emergence Of C Ohridella and Its Parasitoids From Leaf Littsupporting
confidence: 81%
“…Its parasitoid complex (Hymenoptera) includes about 20 species. The most dominant species are Minotetrastichus frontalis (Nees) and Pediobius saulius (Walker) (Hymenoptera: Eulophidae) (Volter & Kenis, 2006;Grabenweger et al, 2007;Cebeci et al, 2011). These two species are also the most abundant parasitoids recorded in the Czech Republic (Zemek et al, 2006).…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the observed diversity of the parasitoid complex was quite low, we consider our Moreth et al 2000;Balász et al 2002;Grabenweger 2002;Lethmayer 2002;Grabenweger et al 2005Grabenweger et al , 2007Lupi 2005;Volter & Kenis 2006). The spectrum of parasitoid species corresponds with previously published data except for one undetermined species of mymarid, which was recorded for the first time from horse chestnut leaves infested by larvae of C. ohridella.…”
Section: Discussionsupporting
confidence: 82%
“…Backhaus et al 2002;Grabenweger 2003;Grabenweger et al 2005aGrabenweger et al , b, 2007Rämert et al 2011). Control measures of the leaf miner populations focus mostly upon mechanical (Gilbert et al 2003;Kehrli & Bacher 2003;Pavan et al 2003) and chemical control (Kuldová et al 2007), however their effectiveness is either short-term or ecologically questionable.…”
mentioning
confidence: 99%